Forecasting Batam City Secondary School Enrolments in 2035: Implementing Double Brown Exponential Smoothing - Pamungkas, Tubagus; Prananto, Irfan Wahyu; Pohan, Albert Efendi; Abd. Ghani, Muhammad Faizal (Jurnal Prima Edukasia, 2025)
Batam City, an industrial hub in the Riau Kepulauan Province, Indonesia, boasts a significant immigrant population and occupies a strategic position along international shipping routes, bordering other nations. The city experiences one of the fastest population growth rates in Indonesia, including a surge in student numbers. The current number of elementary school students and the number of junior high and high school students in the next few years play an important role  for sustainable development, aligning with the government's Golden Indonesia Vision 2045, which aims to cultivate a high-quality and productive generation. To support this initiative, accurate projections of student numbers, particularly in high schools, are essential. This study focuses on forecasting the number of senior secondary school students in Batam City for 2035. Utilizing data from the Batam City Statistics Agency spanning 2019 to 2022. To achieve the research goals, the authors employed the Smoothing Exponential Brown Parameter to project figures for 2023-2035. The optimal projection was achieved with Î±=0.99, estimating 29,988 high school students in Batam City by 2030 and 34,775 by 2035. The research findings indicate that the Batam City government is highly recommended to formulating the policies and planning to establish 18 new secondary schools, addressing potential shortages in classrooms and educational institutions. Additionally, the study urges the local government need to ensure the availability of 1,879 teachers of secondary school by 2035 in Batam City. These projections can assist the administration in effectively planning for educational resources to deliver quality education by 2025, contributing to the realization of the Golden Indonesia Vision 2045